Outbreak of Achromobacter xylosoxidans in an Italian Cystic fibrosis center: genome variability, biofilm production, antibiotic resistance, and motility in isolated strains - Trancassini, Maria; Iebba, Valerio; Citerà, Nicoletta; Tuccio, Vanessa; Magni, Annarita; Varesi, Paola; De Biase, Riccardo Valerio; Totino, Valentina; Santangelo, Floriana; Gagliardi, Antonella; Schippa, Serena (Frontiers in Microbiology, 2014)
Cystic fibrosis (CF) patients have chronic airway infection and frequent exposure to antibiotics, which often leads to the emergence of resistant organisms. Achromobacter xylosoxidans is a new emergent pathogen in CF spectrum. From 2005 to 2010 we had an outbreak in A. xylosoxidans prevalence in our Cystic fibrosis centre, thus, the present study was aimed at deeply investigating virulence traits of A. xylosoxidans strains isolated from infected CF patients. To this purpose, we assessed A. xylosoxidans genome variability by randomly amplified polymorphic DNA (RAPD), biofilm production, antibiotic resistances, and motility. All A. xylosoxidans strains resulted to be biofilm producers, and were resistant to antibiotics usually employed in CF treatment. Hodge Test showed the ability to produce carbapenemase in some strains. Strains who were resistant to β-lactamics antibiotics, showed the specific band related to metal β-lactamase (blaIMP-1), and some of them showed to possess the integron1. Around 81% of A. xylosoxidans strains were motile. Multivariate analysis showed that RAPD profiles were able to predict Forced Expiratory Volume (FEV1%) and biofilm classes. A significant prevalence of strong biofilm producers strains was found in CF patients with severely impaired lung functions (FEV1% class 1). The outbreak we had in our centre (prevalence from 8.9% to 16%) could be explained by an enhanced adaptation of A. xylosoxidans in the nosocomial environment, despite of aggressive antibiotic regimens that CF patients usually undergo.